Effect of Driving Signals on Motion Characteristics of Multilayer Electrostatic Actuator Supported by Only Lubricating Liquid - Md Ghazaly, Mariam (2012)
The present paper describes Effect of Driving Signals on Motion Characteristics of Multilayer Electrostatic Actuator Supported by Only Lubricating Liquid.